2011
DOI: 10.1111/j.1468-5973.2011.00642.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Business Recovery Immediately after Hurricane Katrina

Abstract: Factors contributing to business recovery 6-8 months after Hurricane Katrina were examined. Managers from 183 surviving organizations in the Greater New Orleans area rated the levels of storm preparation, amount of storm damage, severity of storm-related problems and organizational performance. Factors under management's control such as having an emergency response plan, storm preparation and effective staff communication had no real impact on organizational performance. Significant predictors with a negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
118
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(122 citation statements)
references
References 18 publications
2
118
0
2
Order By: Relevance
“…Both infrastructure and social structure broke down severely after Hurricane Katrina [27]. The loss of basic services such as power, natural gas, and clean water made it hard for local businesses to reopen after Katrina.…”
Section: Pre-disaster Business Characteristicsmentioning
confidence: 99%
“…Both infrastructure and social structure broke down severely after Hurricane Katrina [27]. The loss of basic services such as power, natural gas, and clean water made it hard for local businesses to reopen after Katrina.…”
Section: Pre-disaster Business Characteristicsmentioning
confidence: 99%
“…Corey and Deitch (2011) found a significant positive correlation between the loss of customer base and business failure in the wake of hurricane Katrina, a finding further supported by Tierney (2007) and Alesch, Holly et al (2001). The effects of a lower population can also impact the business through staffing (Tierney 2007).…”
Section: ____________________________________________________________mentioning
confidence: 58%
“…Kroll, Landis et al (1991) found that the economic recovery associated with small business in the wake of the Loma Prieta earthquake varied based on industry type and physical location. Further studies support the impact of industry type on survival, providing evidence that the retail sector is often the most vulnerable industry (Kroll, Landis et al 1991, Boarnet 1996, Webb, Tierney et al 2002, Cole, Corbett et al 2005, Wasileski, Rodríguez et al 2011 while construction and manufacturing related industries are more resilient Tierney 1998, Corey andDeitch 2011). These results are not necessarily consistent across the literature (Corey and Deitch 2011) but represent the most common findings.…”
Section: Small Businessmentioning
confidence: 84%
“…Wystąpić mogą przy tym koszty przestoju i utraty zysków. Nawet jeżeli operacje zostają wznowione, fizyczne uszkodzenia w przedsię-biorstwie mogą powodować zmiany w jego wynikach finansowych (Corey, Deitch, 2011). Wystąpienie ekstremów pogodowych powoduje ponadto inne koszty: zmiany dostawcy, relokacji, odtworzenia parku maszynowego (Burnham, 2006).…”
Section: Oddziaływanie Ekstremów Pogodowych Na Przedsiębiorstwaunclassified